PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE STUDENT TEAMS ACHIEVEMENT DIVISION ( STAD ) UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS XI (AKUNTANSI) SMK ROKAN BAGANSIAPIAPI TAHUN AJARAN 2015/2016 - Sudariyanti '; Yustina '; Nursal ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract : This study aimed to improve learning outcomes IPA Accounting class XI student of SMK Bagan Rokan Siapiapi through the implementation of cooperative learning model Student Team Achievement Divisions ( STAD ) which was conducted in March 2016 to April 2016. The sample in this study were students of class XI accounting for 23 students comprising 15 female students and eight male students . The parameters of this study are student learning outcomes and student akitivitas . The research instrument that pembelajara device , a test sheet ( post test and UH ) and student activity observation sheet . The collected data were analyzed descriptively . The results of data analysis showed that the application of cooperative learning model STAD on the learning process can improve student learning outcomes XI IPA Accounting SMK Bagan Rokan Siapiapi the academic year 2015/2016 .Keywords : Cooperative Learning Model STAD , Learning Outcomes , IPA